2016
DOI: 10.5455/ijmsph.2016.07022016398
|View full text |Cite
|
Sign up to set email alerts
|

Measuring undernutrition by composite index of anthropometric failure (CIAF): a community-based study in a slum of Nagpur city

Abstract: Background: In any community, under-five children constitute one of the most vulnerable groups for nutritional deficiencies. The estimation of growth in children is vital for screening health status, identifying divergences from normality, and evaluating the efficiency of interventions. Composite index of anthropometric failure (CIAF) offers a single number to the overall evaluation of malnourished children in a population, which no other conventional indicators do. Objective: To estimate the overall prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
4
20
1
Order By: Relevance
“…et al showed higher rates of composite index of anthropometric failure than compared to the present study. 6,[10][11][12][13][16][17][18]20,[23][24] Further, some studies found similar rates compared to our study. Studies by Bejarano IF et al done in Argentina had very low rates of composite index of anthropometric failure when compared to the present study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…et al showed higher rates of composite index of anthropometric failure than compared to the present study. 6,[10][11][12][13][16][17][18]20,[23][24] Further, some studies found similar rates compared to our study. Studies by Bejarano IF et al done in Argentina had very low rates of composite index of anthropometric failure when compared to the present study.…”
Section: Discussionsupporting
confidence: 82%
“…23 Using this prevalence, with 95% confidence interval and 5% absolute precision the sample size we found was 373. Anticipating a non-response rate of 20%, the final minimum sample size was found to be 448.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…14 Though the higher rate reported by Gupta et al (62%), Rastogi et al (73.4%) and Dhok et al (58.59%). [15][16][17] In the present study, malnutrition among female children compared to male and Muslim children as compared to Hindus were higher, but the association was found insignificant, similar findings were observed in the study by Singh, et al Uttar Pradesh in northern India. 18 Children from low socioeconomic class were significantly malnourished, and similar findings were reported by various other studies.…”
Section: Discussionsupporting
confidence: 78%
“…18 Children from low socioeconomic class were significantly malnourished, and similar findings were reported by various other studies. 1,17,18 In the current study, children who were from less educated mother and with more number of siblings were more likely to have anthropometric failure, Shit et al, Purohit et al, Maharashtra also observed similar findings regarding education level of mother and number of siblings in the family. 19,20 In the present study, malnutrition was more among females than males, among Muslims than Hindus, among children of low socioeconomic status groups, among children of less educated mothers and among those children who were not exclusively breastfed.…”
Section: Discussionsupporting
confidence: 74%